Definitions of energy poverty and policies to reduce it - Bacon, R (Oxford Institute for Energy Studies, 2010)
Globally, energy poverty is extremely widespread, and projections suggest that, without aggressive policies to counter it, the level of energy poverty will remain high for many years to come. A commonly accepted and simple definition of energy poverty is that a household without access to electricity or clean modern fuels is energy poor. However, even in this definition the notion of access differs between users. Access to an energy source is generally understood to mean that the infrastructure to deliver that source exists in the neighbourhood of the house (e.g. there are electricity connections in the village or neighbourhood).